PWE-173 Investigation of volatile organic compounds emitted from faeces for the diagnosis of giardiasis. (22nd June 2015) - Bond, A; Vernon, A; Reade, S; Mayor, A; Wastling, J; Minetti, C; Lamden, K; Probert, C
Abstract : Introduction: Giardiasis is a common but neglected intestinal infection worldwide, caused by the flagellated intestinal protozoan Giardia duodenalis (syn. lamblia/intestinalis ). Several methods are available for the laboratory diagnosis of Giardia . It has unique metabolic pathways related to its lack of mitochondria, making it an ideal target for volatile organic compound profiling. Method: Faecal gas headspace extraction and Gas Chromatography-Mass Spectrometry (GCMS) were used to extract and identify VOCs. Analytical tools including Metab, 1 R and Metaboanalyst 2 were subsequently used. Stool was obtained from patients with confirmed isolated Giardia infection, together with stool from subjects with diarrhoea but no identifiable infection, including Giardia, these acted as controls. Significant differences between the VOCs were then analysed. Results: The composition of these compounds was dominated by Esters, Acids and Alcohols, respectively. With an absence of Amides, Alicyclic compounds, Ether compounds and Nitrogen Containing compounds. >100 VOCs were identified across both the control and Giardia groups. Of these 10 were noted to be significantly different between the two groups (p < 0.01). Three VOCs were identified with a significant predominance to the Giardia samples, 2, 2, 4, 4-tetramethyloctan, acetic acid and 2, 2, 4, 6, 6-pentamethylhepatance (p < 0.0001). 10 VOCs were found to be significantly different in terms of abundance (p < 0.01), acetone and 2-butanone were the two most significantly different compounds, both demonstrating a p value of <0.001 and both having down regulation in the Giardia samples. PLS-DA showed a good degree of separation. AUROC analysis gave 5 VOCs with an AUC between 0.8 and 0.93. Conclusion: There is a significant difference in the VOC profile of stool from subjects infected with Giardia spp, when compared to non-infected controls, both in terms of prevalence and abundance. There is also a defined metabolic reason for this difference originating from the unique metabolic pathways seen in Giardia . Disclosure of interest: None Declared. References: Aggio R, Villas-Bôas SG, Ruggiero K. Metab: an R package for high-throughput analysis of metabolomics data generated by GC-MS. Bioinformatics (Oxford, England) 2011;27 :2316–2318. doi:10.1093/bioinformatics/btr379 Xia J, Psychogios N, Young N, and Wishart DS. MetaboAnalyst: a web server for metabolomic data analysis and interpretation. Nucl Acids Res. 2009;37:W652–660.